POLEMIK PILKADA SERENTAK 2020: PERJUANGAN PELAKSANAAN PERHELATAN DEMOKRASI DI TENGAH PANDEMI COVID-19 (Jurnal Bawaslu Provinsi Kepulauan Riau, 2021)
Back on the 2nd of March 2020, The Republic of Indonesia’s leader, Joko Widodo, officially declared the first case of Coronavirus Disease (“COVID-19”) in Indonesia. Based on the data from the World Health Organization (“WHO”), COVID-19 is an infectious disease which is caused by a new type of coronavirus. In order to minimize the virus transmission, the government enacted the “Pembatasan Sosial Berskala Besar” or known as “large-scale social restrictions” policy in several areas. In implementing its regulation, several public activities are restricted, such as educational activities, workplaces, religious activities, and public facilities. However, in contrast to the implementation of Regional Elections in 2020, this democracy event was kept going by involving the role of Indonesians massively to implement the democratic system. The execution of this event raised a debate among citizens and the government. This paper aims to review and analyze the evaluation of Regional Elections which was held on December 9th, 2020.